IMMUNOMODULATION EFFECT OF LEVAMISOLE AND IMMULITE ON UTERINE MICROBIAL PICTURE IN REPEAT BREEDING COWS - KSWAIN, P; MOHANTY, D N; DAS, S; BARIK, A K; MISHRA, P C; TRIPATHY, A K; PALAI, T K (The Indian Journal of Animal Reproduction, 2011)
Forty (40) cyclic non breeding cows presented at lVCC were assigned to four equal (10) groups Levamisoles/c. three injections at weekly interval@ 2.5 mg/kg body weight (group I), lmmulite an herbal drug 20 ml orally for1 0 days (group II), combination therapy of levamisole + immulite with same dose schedule (group Ill) was administeredTen animals subjected to saline uterine lavage (60 ml lukewarm normal saline) served as control (group IV} Thetotal serum immunoglobulin (lg) and uterine bacterial load were estimated at estrus before initiation of treatmentand at subsequent estrus following treatments. The conception rate for each treatment regimen was also evaluatedThe pretreatment total lg values (gms I di) were 1.95±0.07, 1.93±0.05, 1.90±0.06, 1.91±06 in group I, II, Ill and IVrespectively with corresponding post treatment value* of 2 .3 7 ±0.04, 2.16±0 .05, 2.46±0. 05 and 1. 75±0. 05. The posttreatment values in different experimental groups except control were significantly elevated (P
Keywords: lmmunomodulators; Levamisole; lmmulite; Repeat Breeding, lmmunoglobulin